Early colonization of the deep-sea bottom—The protracted build-up of an ecosystem - Luis A. Buatois; M. Gabriela Mángano; Maximiliano Paz; Nicholas J. Minter; Kai Zhou (Proceedings of the National Academy of Sciences, 2025)
Our understanding of the patterns and processes behind the evolution of deep-marine ecosystems is limited because the body-fossil record of the deep sea is poor. However, that gap in knowledge may be filled as deposits are host to diverse and abundant trace fossils that record the activities of benthic deep-marine organisms. Here, we built a global dataset of trace-fossil occurrences from a comprehensive survey of 720 Ediacaran–Devonian units and show that the establishment of a modern-style deep-marine benthic ecosystem was protracted and coincident with global cooling and increase in oxygenation during the Ordovician. The formation of open burrows may have increased bioirrigation in the uppermost sediment zone, promoting ventilation and generating an ecosystem engineering feedback loop between bioturbation and pore-water oxygenation. Sharp changes in deep-marine bioturbation during the Devonian may have originated from oxygen variations resulting from climate-controlled oceanic circulation.